2012
DOI: 10.1007/s10704-011-9664-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of intergranular and transgranular crack propagation in ferroelectric polycrystals

Abstract: We present a phase-field model to simulate intergranular and transgranular crack propagation in ferroelectric polycrystals. The proposed model couples three phase-fields describing (1) the polycrystalline structure, (2) the location of the cracks, and (3) the ferroelectric domain microstructure. Different polycrystalline microstructures are obtained from computer simulations of grain growth. Then, a phase-field model for fracture in ferroelectric single-crystals is extended to polycrystals by incorporating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 50 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…Observation on microcracks in this study thus provides an insight into the development of AE events in the faulting (shear fracturing) process. As a result, more energy should be released in the former since the energy release rate of transgranular crack is usually several times of that of grain boundary crack (Abdollahi & Arias, 2012;Alber & Hauptfleisch, 1999;Tatami et al, 1997;Yasuda et al, 1993). A shear fracturing first exhibits a larger total microcrack density and a wider damage zone than a tensile fracturing.…”
Section: Implications To Seismic Activitymentioning
confidence: 99%
“…Observation on microcracks in this study thus provides an insight into the development of AE events in the faulting (shear fracturing) process. As a result, more energy should be released in the former since the energy release rate of transgranular crack is usually several times of that of grain boundary crack (Abdollahi & Arias, 2012;Alber & Hauptfleisch, 1999;Tatami et al, 1997;Yasuda et al, 1993). A shear fracturing first exhibits a larger total microcrack density and a wider damage zone than a tensile fracturing.…”
Section: Implications To Seismic Activitymentioning
confidence: 99%
“…In the same way, additional bulk energy terms, such as the chemical free energy density f chem (c, φ s ) (see Eq. (19). (7)), can easily be included in the total energy functional of Eq.…”
Section: Multiphase-field Model Based On Griffith's Theorymentioning
confidence: 99%
“…By minimization of the total system energy, the models describe the propagation of cracks [7]. Extensions of this approach to plastic effects in multiphase materials are elaborated by Schneider et al [18] and applications in ferroelectric polycrystals are shown by Abdollahi and Arias [19]. Only few approaches describe crack propagation in heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter work, crack propagation was linked to an anisotropic fracture toughness that enters the model by means of an anisotropic crack-surface-density function (see also Teichtmeister et al [6] for more details). Phase-field models for crack propagation in ferroelectrics in consideration of domain evolution have been proposed by, for example, Xu et al [11] and Abdollahi et al [12][13][14]. [8] who confirmed that an applied electric field influences the material's fracture toughness.…”
Section: Introductionmentioning
confidence: 99%